Interpersonal trust during childhood and adolescence - Rotenberg, Ken J. (Cambridge : The University Press, 2010)
Since the beginnings of psychology as a discipline, interpersonal trust has been regarded as a crucial aspect of human functioning. Basic levels of interpersonal trust amongst people were believed to be necessary for the survival of society and the development of successful psychosocial functioning. Some research has shown that interpersonal trust is linked to physical health, cognitive functioning, and social functioning (including close relationships) across development. This book presents the current research in the growing field of interpersonal trust during childhood and adolescence (up to the onset of adulthood). It deals with the extent to which children and adolescents demonstrate the multiple facets of trust and trustworthiness, and how these multiple facets affect their social relationships with a wide range of social contacts: parents, peers, and social groups. It will be of interest to developmental, social, educational and clinical psychologists
Includes bibliographical references and index
Keywords: Trust; Children; Teenagers